2017
DOI: 10.1093/mnras/stx2546
|View full text |Cite
|
Sign up to set email alerts
|

Initial velocity V-shapes of young asteroid families

Abstract: Ejection velocity fields of asteroid families are largely unconstrained due to the fact that members disperse relatively quickly on Myr time-scales by secular resonances and the Yarkovsky effect. The spreading of fragments in a by the Yarkovsky effect is indistinguishable from the spreading caused by the initial ejection of fragments. By examining families <20 Myrs-old, we can use the V-shape identification technique to separate family shapes that are due to the initial ejection velocity field and those that a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The limits of the V-shape region then correspond to cos θ = ±1. Data for the Karin and Koronis (Nesvorný et al 2002;) families suggest that αEV ≃ 1 (see also Bolin et al 2018). Therefore, if we assume that the V-shape for the Nele family in the (a, 1/D) domain observed in Sect.…”
Section: Age Estimates Of the Nele Familymentioning
confidence: 95%
“…The limits of the V-shape region then correspond to cos θ = ±1. Data for the Karin and Koronis (Nesvorný et al 2002;) families suggest that αEV ≃ 1 (see also Bolin et al 2018). Therefore, if we assume that the V-shape for the Nele family in the (a, 1/D) domain observed in Sect.…”
Section: Age Estimates Of the Nele Familymentioning
confidence: 95%
“…In addition, the Yarkovsky effect is able to transport meter-scale objects like 2020 CD 3 into the proximity of the n 6 resonance, the most likely source of 2020 CD 3 , in <1 Myr if it were to have originated as a fragment at 2.3 au (Bottke et al 2006;Vokrouhlický et al 2015), where most V-type asteroids are found, even if possesses significantly different thermal inertia properties compared to larger, kilometer-scale asteroids (Delbo et al 2007;Bolin et al 2018a). In addition, is apparent from the wide distribution of the 1 km Vesta family fragments covering the entirety of the inner Main Belt (Bolin et al 2017) that the size-dependent velocity distribution of family fragments originating from Vesta could have placed 2020 CD 3 -sized objects anywhere between the nu 6 resonance at ∼2.2 au and the 3:1 resonance at 3.5 au (Carruba & Nesvorný 2016;Bolin et al 2018b). Therefore, the location of the n 6 resonance at the inner edge of the Main Belt at 2.2 au as the most likely source of 2020 CD 3 does not necessarily preclude asteroids far from its vicinity as the original parent body of 2020 CD 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In this work we explicitly test this and try to define which values are optimal as a function of . Bolin et al (2018b) took a more elegant approach whereby asteroids in each sliver where weighted by the asteroid belt SFD, such that the few number of larger asteroids were weighted more than the many more smaller asteroids. Which SFD is to be used; that presumed for a family just after formation, or the current SFD of the asteroid belt; is one parameter, where minimum and maximum sizes of asteroids are potentially additional parameters.…”
Section: Detection Toolsmentioning
confidence: 99%
“…An approach that would also possibly result differently for the w prediction is weighting the objects diameters within the data set used for the search. This technique, not considered in the present work, was developed by Bolin et al (2018b) and consists in giving more importance for the large diameter objects above the nominal V, rather than accounting for every object as we do. Therefore, although the strategy used by Delbó et al (2017Delbó et al ( , 2019 is correct and should be used in every case where physical properties are well known, as well as that from Bolin et al (2018b) (certainly a much better approach to characterize the precise slope of the family/signal found by any method or data selection), our method intention is to characterize the best set of parameter that most efficiently return a signal that well represents a family slope and center, while being more general and less dependent on data selection.…”
Section: W As Function Of K; Both Side Scoring In the Wℎmentioning
confidence: 99%